Dry Socket following Extraction of Permanent Teeth. A Study (Medical Forum Monthly, 2024)
Objective: To find out frequency and clinical presentation of dry Socket following extraction of permanent teeth among patients at Liaquat University hospital Hyderabad.Study Design: Retrospective StudyPlace and Duration of Study: This study was carried out at department of oral & maxillofacial surgery Liaquat university hospital Hyderabad from May 2012 to May 2013.Materials and Methods: Patients of both genders and all ages were included in the study. They were observed for the presence of dry socket. Patients with previous history of two or more days of extraction, pain, sensitivity on gentle probing of the extraction socket and empty / partially empty socket / halitosis were included in the study. Data was analyzed using SPSS version-17.Results: A total of 1540 patients who underwent extraction of permanent teeth for various reasons were studied. There were 960 male patients and 580 female patients. Dry socket was found in 110 patients. 64 were male patients and 46 were female patients. Majority of patients were in 3rd decade of life. Mandibular first molar was affected in 42 patients followed by Mandibular 3rd molar in 29 patients. Pain and sensitivity on gentle probing was found in all patients, complete empty socket in 49 patients, partially empty socket in 61 patients and halitosis in 16 patients.Conclusion: Treatment of dry socket are inadequate and aimed at to soothing. Dry socket site should be irrigated with hot saline packing with a BIPP. Zinc oxide–eugenol paste can be relieving pain.